Currículo, Infância e Educação Corporal: Fundamentos na perspectiva histórico-cultural e orientações no campo da interdisciplinaridade - Santos, Cristiane Aparecida Silveira [UNESP] (2016)
In the present study aimed to, through action research with a basic education teachers group Children's Municipal System of Education Bauru initially analyzed the pedagogical practice considering the knowledge of the Pedagogical Political Project to guide the process teaching and learning, planning of the contents, objectives and procedures and the relationship between space, time and material in Motion area of expertise in early childhood education with the main purpose to propose a reasoned curriculum from the perspective of historical-cultural approach and curriculum guidelines in Interdisciplinary field of / in childhood, aiming to guide the teaching practice of generalist teachers who teach children of four and five belonging to the Basic Education - Child. To this end, it was carried out a literature review covering up aspects: a) the historical social construction of Brazilian education, childhood, body and Early Childhood Education in Brazil, b) curriculum design in / childhood from a proposal for interdisciplinary curriculum in view of the historical-cultural approach. With regard to the methodology, a research based on an analysis from a qualitative approach was carried out. For this investigative category, it was used action research, with a focus group of teachers who work with early childhood education. To complement the survey instrument, it was used as a descriptive questionnaire and a semi-structured interview. Research showed the limitations and difficulties of generalist teachers in relation to the movement area. It was found to possess an empirical approaches to the planning and teaching-learning organization and it was concluded that these limitations and difficulties are arising from the initial training does not include training in this area and the lack of interest in seeking remedy these faults in the continuing education that lead to practices of mere recreational and play activities uncompromised with a good education that enables full child development. Therefore, as a result of action research, carried out the steps / stages of collection, analysis, reflections, was generated the Educational Project in the Perspective of Historical-Cultural Approach and Curriculum Guidelines at the Interdisciplinary Course. For the generation of this project was carried out a methodological theoretical study on the matters necessary for the construction of this project.